Peran Augmented Reality dan Mobile Marketing dalam Meningkatkan Promosi Bisnis - Selly Puspita Sari; Cintya Sukma Widita; Bayu Sekar Larasati; Ulfa Isni Kurnia; Alfina Alfina (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This community service activity aims at preparing students to utilize technological developments that are used to improve business promotion at SMK Ma Arif Banyumas through the role of augmented reality and mobile marketing. Research Methodology: This mentoring process is carried out by socializing the use of digital technology as a medium for business promotion. The target of this community service is 12th-grade students of SMK Ma Arif Banyumas, with specifications majoring in Office Management and Business Services. Results: The result of this community service is to educate and provide solutions for students in developing businesses through a technology-based promotional medium, which in this case is through the role of augmented reality and mobile marketing. Conclusions: Augmented reality provides users with an overview of the merging of the real world and the virtual world. Meanwhile, mobile marketing focuses on what media and content you need to design to promote and become a medium of communication to consumers. Limitations: This research is still in the socialization stage, so it is necessary to have an implementation process from the results of the first stage of socialization. Contribution: This research contributes to SMK Ma Arif Banyumas in utilizing technological developments that are used to enhance business promotion through the role of augmented reality and mobile marketing.